gambaran perilaku pemeliharaan kesehatan gigi dan mulut mahasiswa okupasi terapi poltekkes surakarta selama pandemi covid-19 - Fitri Suviati; Neneng Nurjanah; Tri Widyastuti; Denden Ridwan Chaerudin (Poltekkes Kemenkes Bandung, 2021)
Dental and oral health can affect the health of a person's body because through this organ various germs can enter. Therefore, the discipline of maintaining dental and oral health is essential for the well-being of the individual. Thorough cleaning of the mouth is a major component in the maintenance of dental and oral health. With mechanical and chemical assistance, you can clean your teeth and mouth such as brushing your teeth after breakfast and before bed, eating foods and drinks that are good for your teeth and using tools such as mouthwash and dental floss. The purpose of this study is to know the description of dental and oral health maintenance behavior of students occupational therapy poltekkes ministry of Surakarta during the Covid-19 pandemic. This research is a descriptive research conducted in January-June 2021. The number of samples of 38 people using purposive sampling technique. Analysis using frequency distribution. Result: The results of the analysis on the sample of students occupational therapy Poltekkes Kemenkes Surakarta showed that 92.1% of respondents have dental and oral health maintenance behaviors with good criteria, 94.7% have good brushing behavior, 77.7% have good behavior in consuming food and beverages that are good for dental health and 65.8% have bad behavior in the use of tools to help. Conclusion: The majority of respondents have dental bad oral health maintenance behavior with good criteria.